Tradition of Khanduri Peutron Bijeh Keubeu Jagat in Gampong Baro Village, Teunom, Aceh Jaya District: Tradisi Khanduri Peutron Bijeh Keubeu Jagat di Gampong Baro Kecamatan Teunom Aceh Jaya - Syakhlis Ilham Nusra; Nuraini A Manan (Indonesian Journal of Islamic History and Culture, 2024)
The Khanduri Peutron Bijeh Keubeu Jagat tradition is an event held periodically every three years before the seed sowing season. This tradition is part of the activities of the Mukim Teunom community which takes place in Gampong Baro Village, Kemukiman Teunom. This study aims to explore more deeply the process of implementing this tradition, the meaning contained in it, and the community's response to this phenomenon. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the Khanduri procession is carried out in the morning with the slaughter of the keubeu jagat animal along with the reading of prayers at the Khanduri location. The Khanduri Peutron Bijeh Keubeu Jagat tradition is held as an effort to ask God to keep wild animals away from human settlements, protect rice fields and gardens from pest attacks, and provide hope for an abundant harvest. Community participation in this tradition is very high because it is considered to have great benefits, such as protection from danger when fishing in the sea or when gardening from tiger attacks, and protecting agriculture from pest attacks. In addition, this Khanduri is also a momentum to strengthen social relations between the Teunom Settlement community, maintaining harmony and cooperation between them